If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 1) + 9 = 5x + -26 Reorder the terms: 5(1 + 3x) + 9 = 5x + -26 (1 * 5 + 3x * 5) + 9 = 5x + -26 (5 + 15x) + 9 = 5x + -26 Reorder the terms: 5 + 9 + 15x = 5x + -26 Combine like terms: 5 + 9 = 14 14 + 15x = 5x + -26 Reorder the terms: 14 + 15x = -26 + 5x Solving 14 + 15x = -26 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 14 + 15x + -5x = -26 + 5x + -5x Combine like terms: 15x + -5x = 10x 14 + 10x = -26 + 5x + -5x Combine like terms: 5x + -5x = 0 14 + 10x = -26 + 0 14 + 10x = -26 Add '-14' to each side of the equation. 14 + -14 + 10x = -26 + -14 Combine like terms: 14 + -14 = 0 0 + 10x = -26 + -14 10x = -26 + -14 Combine like terms: -26 + -14 = -40 10x = -40 Divide each side by '10'. x = -4 Simplifying x = -4
| 2(2x+5)-1=1 | | 3(a+4)=3 | | 2(5x+1)=-4x-40 | | 1/2(t-6)=1 | | 1/3(4d+6)=12d | | 2/3(g-4)=12 | | 10y=6y+9+3y | | y=4x^3-5x^2 | | -x+2+2x=2x+7 | | -215+e+(-43)=-45 | | 3(w-7)=1+2w | | 3x+6=4-5x | | 3y(y+1)=2(y-3) | | 3x+4-6x=5 | | ln(x-3)=14 | | 6w+7=8 | | -2-6p+p-2=7-p | | 5p-33=2(p-3) | | b-2.7=-2+2b | | 3x-7x-11=-4x+3-11 | | 78-2x=-3+8 | | x^2+1.5x-7=0 | | 3(2.47x+1.23)=9.82 | | 7=-3-2c | | 8-(2y-1)=3-3y | | 2x-4.2=8.6 | | 10x-7+3x-4=9x-3+3x | | -5-3m=-14 | | x/4=x-12 | | -9(m-7)+2(2-4m)=-18(m-3)+3 | | m^2-8m^1-9=0 | | -4d-15=-3(d+5)-d |